The debt eaudiobook The story of a past redeemed. - Hunt, Angela (Recorded Books Inc., 2015)
In this life-changing tale, Christy Award winner Angela Hunt delivers a bittersweet "wake-up call that should jolt many . out of complacency" (Publishers Weekly). Seventeen-year-old Emma suddenly finds her sordid life miraculously transformed by God's redeeming grace. She soon marries a godly young man who eventually becomes a nationally recognized preacher with a television audience of 50 million. But after 24 years as an exemplary pastor's wife, one call changes everything.